Strategic Leadership: Values, Styles, and Organizational Performance. (November 2013) - Carter, Suzanne M.; Greer, Charles R.
Strategic leaders are being challenged by stakeholder demands that organizations meet triple bottom line performance measures. Nonetheless, there is a paucity of empirical research on how strategic leaders' values and leadership styles are related to such measures. We describe values and established and evolving leadership styles and review the results of empirical studies investigating their relationship with organizational performance. Gaps in our knowledge of such relationships are identified and suggestions for future research are provided. A continuum of leadership styles, from transactional through responsible, is developed using the dimensions of stakeholder salience and economic, social, and environmental performance outcomes.